Efektivitas Penggunaan Metode Audiolingual Dalam Pembelajaran Bahasa Arab - Nurul Hanani (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2016)
The development of language teaching method continuously develops fast. However, a classical language teaching method is still commmonly used in learning activity of language classes. This article investigates the classical method which is still used by a course institution of OCEAN Pare, Kediri namely Audiolingual method, and how effective the method is for developing language skills. This research employes fenomenology approach in which the researcher tries to understand the meaning of an even and the relations toward the people in a certain situation. The finding shows that the use of audiolingual method in learning Arabic language in OCEAN Pare, Kediri has been implemented in many years and resulted some students having good skills in Arabic language.